2022
DOI: 10.1093/pcp/pcac042
|View full text |Cite
|
Sign up to set email alerts
|

SQUINT Positively Regulates Resistance to the Pathogen Botrytis cinerea via miR156–SPL9 Module in Arabidopsis

Abstract: SQUINT (SQN) regulates plant maturation by promoting the activity of miR156, which functions primarily in the miR156–SQUAMOSA PROMOTER BINDING PROTEIN-LIKE9 (SPL9) module regulating plant growth and development. Here, we show that SQN acts in the jasmonic acid (JA) pathway, a major signaling pathway regulating plant responses to insect herbivory and pathogen infection. Arabidopsis thaliana sqn mutants showed elevated sensitivity to the necrotrophic fungus Botrytis cinerea compared with wild type. However, SQN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 70 publications
1
6
0
Order By: Relevance
“…Most of known miRNAs and their function were consistent with previous work, such as miR156, miR159, miR171, miR5300, and miR6027 which were involved in plant immunity [ 9 , 34 , 35 , 36 ]. Some miRNAs could regulate R genes in plants directly, the miR482 family (stu-miR482a/d/e-3p and stu-miR482) mainly regulates NBS-LRR genes in eudicots, functioning as an essential component in plant disease resistance [ 37 ]; miR6024-3p regulates NLR genes to facilitate the disease caused by the necrotrophic pathogen [ 38 ].…”
Section: Discussionsupporting
confidence: 87%
“…Most of known miRNAs and their function were consistent with previous work, such as miR156, miR159, miR171, miR5300, and miR6027 which were involved in plant immunity [ 9 , 34 , 35 , 36 ]. Some miRNAs could regulate R genes in plants directly, the miR482 family (stu-miR482a/d/e-3p and stu-miR482) mainly regulates NBS-LRR genes in eudicots, functioning as an essential component in plant disease resistance [ 37 ]; miR6024-3p regulates NLR genes to facilitate the disease caused by the necrotrophic pathogen [ 38 ].…”
Section: Discussionsupporting
confidence: 87%
“…Recent studies showed that the miR156-SPL pathway involved in plant immunity. Disrupting miR156 function in Arabidopsis by mutating SQUINT (SQN), an Arabidopsis orthologue of cyclophilin 40, compromised jasmonic acid signaling and disease resistance against necrotrophic pathogen Botrytis cinerea [ 26 ]. Furthermore, overexpressing miR156-targeted SPL9 in juvenile plants enhanced accumulation of reactive oxygen species and induced salicylic acid (SA) signaling, leading to enhanced resistance of Arabidopsis against bacterial pathogen Pseudomonas syringae [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies showed that the miR156-SPL pathway involved in plant immunity. Disrupting miR156 function in Arabidopsis by mutating SQUINT (SQN), an Arabidopsis orthologue of cyclophilin 40, compromised jasmonic acid signaling and disease resistance against necrotrophic pathogen Botrytis cinerea (27). Furthermore, overexpressing miR156-targeted SPL9 in juvenile plants enhanced accumulation of reactive oxygen species and induced salicylic acid (SA) signaling, leading to enhanced resistance of Arabidopsis against bacterial pathogen Pseudomonas syringae (28).…”
Section: Introductionmentioning
confidence: 99%